Preparation of GNPs thermally conductive adhesive at different epoxy resin/curing agent ratio and mixing method - Jasmee, Solehah; Omar, Ghazali; Che Othaman, Siti Syahirah; Kamarolzaman, Anita Akmar; Masripan, Nor Azmmi; A. Hamid, Husna (Universiti Malaysia Perlis, 2021)
Reinforcement of GNPs fillers to polymer composite show remarkable improvement in thermal conductivity. However, high aspect ratio of GNPs attributes to agglomerate during the preparation process, which limits its performance. A proper step methodology is in urgent need to improve the interfacial reaction between the polymer matrix and fillers. The factors that play a significant role during preparation are controlling the epoxy resin/curing agent ratio (stoichiometry ratio) to ensure complete curing reaction and an appropriate mixing and processing method to improve dispersion and distribution of fillers. This study focuses on the effect of varying the ratio of polymer/curing agent to its curing reaction and combining the mixing method with solvent-free approach on the performance of the polymer composite. The results show that a complete curing reaction was observed at its stoichiometry ratio, which is ratio 3:1. The GNPs fillers also founded distribute and disperse well, especially when using BS+PCTM at the ratio of 3:1. This mixing method can avoid agglomeration of fillers and improve the interfacial reaction with good contact between filler-filler interface. As a result, the thermal conductivity of BS+PCTM was enhanced compared to BS+UH. The results presented perhaps facilitated improvement in the preparation of high performance of TCA